Cyber Practices What Can the U.S. Air Force Learn from the Commercial Sector? - Schmidt, Lara (RAND Corporation, 2015)
This report describes commercial practices for cyber workforce management and organization, as determined from a literature review and interviews with reputable organizations that have similarities to the U.S. Air Force (USAF). These practices are applicable to USAF as it endeavors to improve the management of its cyber forces. The authors describe the basis for each practice, the benefits it conveys, and how it could be implemented by USAF.